Outcomes after right ventricular outflow tract reconstruction with valve substitutes: A systematic review and meta-analysis - Wang, Xu; Bakhuis, Wouter; Veen, Kevin M.; Bogers, Ad J. J. C.; Etnel, Jonathan R. G.; van Der Ven, Carlijn C. E. M.; Roos-Hesselink, Jolien W.; Andrinopoulou, Eleni-Rosalina; Takkenberg, Johanna J. M. (Frontiers in Cardiovascular Medicine, 2022)
Introduction This study aims to provide an overview of outcomes after right ventricular outflow tract (RVOT) reconstruction using different valve substitutes in different age groups for different indications. Methods The literature was systematically searched for articles published between January 2000 and June 2021 reporting on clinical and/or echocardiographic outcomes after RVOT reconstruction with valve substitutes. A random-effects meta-analysis was conducted for outcomes, and time-related outcomes were visualized by pooled Kaplan–Meier curves. Subgroup analyses were performed according to etiology, implanted valve substitute and patient age. Results Two hundred and seventeen articles were included, comprising 37,078 patients (age: 22.86 ± 11.29 years; 31.6% female) and 240,581 patient-years of follow-up. Aortic valve disease (Ross procedure, 46.6%) and Tetralogy of Fallot (TOF, 27.0%) were the two main underlying etiologies. Homograft and xenograft accounted for 83.7 and 32.6% of the overall valve substitutes, respectively. The early mortality, late mortality, reintervention and endocarditis rates were 3.36% (2.91–3.88), 0.72%/y (95% CI: 0.62–0.82), 2.62%/y (95% CI: 2.28–3.00), and 0.38%/y (95%CI: 0.31–0.47) for all patients. The early mortality for TOF and truncus arteriosus (TA) were 1.95% (1.31–2.90) and 10.67% (7.79–14.61). Pooled late mortality and reintervention rate were 0.59%/y (0.39–0.89), 1.41%/y (0.87–2.27), and 1.20%/y (0.74–1.94), 10.15%/y (7.42–13.90) for TOF and TA, respectively. Endocarditis rate was 0.21%/y (95% CI: 0.16–0.27) for a homograft substitute and 0.80%/y (95%CI: 0.60–1.09) for a xenograft substitute. Reintervention rate for infants, children and adults was 8.80%/y (95% CI: 6.49–11.95), 4.75%/y (95% CI: 3.67–6.14), and 0.72%/y (95% CI: 0.36–1.42), respectively. Conclusion This study shows RVOT reconstruction with valve substitutes can be performed with acceptable mortality and morbidity rates for most patients. Reinterventions after RVOT reconstruction with valve substitutes are inevitable for most patients in their life-time, emphasizing the necessity of life-long follow-up and multidisciplinary care. Follow-up protocols should be tailored to individual patients because patients with different etiologies, ages, and implanted valve substitutes have different rates of mortality and morbidity. Systematic review registration [www.crd.york.ac.uk/prospero], identifier [CRD42021271622].